BIOCHEMICAL PROFILE OF PATIENTS WITH ORGANOPHOSPHORUS POISONING: REPORT FROM A RURAL-BASED TEACHING HOSPITAL IN EASTERN INDIA - Roy, Utsab; Gayen, Biplab Kumar; Kar, Jugal Kishore; Dhua, Aparup; Mahapatra, Umakanta; Patra, Manas (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Organophosphorus (OP) poisoning is a very common form of poisoning, especially in rural areas due to the use of OP poisons for agricultural purposes. There is high mortality and morbidity among patients with a history of consumption of this poison. This study aimed to find various biochemical test parameters among patients with OP poisoning admitted to a hospital in the state of West Bengal, India. Methods: This was an observational and cross-sectional study and conducted from January 2020 to July 2021. During the study period, any patients admitted to general medicine with a history of OP poisoning were included in the study. Aseptically collected venous blood was collected on admission, 12 h, 24 h, and 48 h of admission and immediately sent to the central laboratory for analysis in an automated analyzer. Results: A total of 100 patients were analyzed. Among them, 80 patients were alive and 20 patients died. The majority of the patients were young adults (21–30 years [53%]). Among the patients, 64% were male, 91% were rural inhabitants, and 43% were a farmer in the profession. The level of hemoglobin was higher, total WBC count was lower, liver enzymes were lower, and urea and creatinine were lower among the patients who survived. However, the sodium, potassium, and calcium were not significantly different between dead and alive patients. Conclusion: In the management of OP poisoning, the biochemical profile of blood may help identify the patients at risk, and appropriate management can be started accordingly. The biochemical profile also helps in the prognosis of OP poisoning.